2011
DOI: 10.1007/s10354-011-0906-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical factors influencing the beginning and development of osteoarthritis in the hip joint

Abstract: Osteoarthritis (OA) can be used as a common name for a group of overlapping pathological conditions when the balance between the processes of degradation and synthesis, in individual parts of the cartilage, is disturbed and leads to gradual cartilage destruction. A preventive approach toward OA helps with a timely diagnosis and subsequent treatment of this disease. One of the significant risk factors affecting development of hip joint OA is the mechanism and magnitude of mechanical loading on the joint. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Accumulated inadequate loads may further play a role in disease progression, as they can facilitate enlargement of the joint surface that is worn down [29,59,60]. A relevant factor in this aspect is the reduced range of passive hip joint extension we found for the hip OA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated inadequate loads may further play a role in disease progression, as they can facilitate enlargement of the joint surface that is worn down [29,59,60]. A relevant factor in this aspect is the reduced range of passive hip joint extension we found for the hip OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with early stage hip OA, the number of studies is far less [27,28], emphasizing this challenge even more. However, as it has been argued that adequate exercise and muscular strengthening can contribute to reduce abnormal joint loading in hip OA, and, hence, impede disease progression [29], early identification of deviant gait characteristics is crucial in order to develop targeted rehabilitation interventions for patients with hip OA.…”
Section: Introductionmentioning
confidence: 99%
“…This notion is true also from a biomechanical context. Whereas adequate mechanical loading is a vital stimulus for joint homeostasis; cumulative stress caused by abnormal joint loading conversely may have a negative influence on joint deterioration and disease progression in lower limb OA [4,31-33]. However, the contribution of specific biomechanical factors remains unclear [34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from our research group reported the presence of distinct gait alterations at an early stage of disease; as hip OA patients revealed significantly reduced gait velocity, sagittal plane joint excursion and hip extension moment compared to healthy controls [3]. Studies examining whether gait biomechanics in early stage hip OA alter following exercise therapy interventions are of high clinical interest, due to the inherent potential of biomechanics as a target to impede disease progression [4]. However, no such studies exist.…”
Section: Introductionmentioning
confidence: 99%
“…Ground reaction forces provide indirect information about internal joint loading [30]. Ground reaction forces have been used to quantify atypical limb loading for individuals before and after hip arthroplasty [31], [32]. Instrumented force shoes (IFS) are suitable for the measurement of GRF during different tasks [32]- [36].…”
Section: Introductionmentioning
confidence: 99%